What Laboratory Tests and Physiologic Triggers Should Guide the Decision to Administer a Platelet or Plasma Transfusion in Critically Ill Children and What Product Attributes Are Optimal to Guide Specific Product Selection? From the Transfusion and Anemia EXpertise Initiative–Control/Avoidance of Bleeding. (January 2022) - Delaney, Meghan; Karam, Oliver; Lieberman, Lani; Steffen, Katherine; Muszynski, Jennifer A.; Goel, Ruchika; Bateman, Scot T.; Parker, Robert I.; Nellis, Marianne E.; Remy, Kenneth E.
Abstract : Objectives: To present consensus statements and supporting literature for plasma and platelet product variables and related laboratory testing for transfusions in general critically ill children from the Transfusion and Anemia EXpertise Initiative–Control/Avoidance of Bleeding. Design: Systematic review and consensus conference of international, multidisciplinary experts in platelet and plasma transfusion management of critically ill children. Setting: Not applicable. Patients: Critically ill pediatric patients at risk of bleeding and receiving plasma and/or platelet transfusions. Interventions: None. Measurements and Main Results: A panel of 10 experts developed evidence-based and, when evidence was insufficient, expert-based statements for laboratory testing and blood product attributes for platelet and plasma transfusions. These statements were reviewed and ratified by the 29 Transfusion and Anemia EXpertise Initiative - Control/Avoidance of Bleeding experts. A systematic review was conducted using MEDLINE, EMBASE, and Cochrane Library databases, from inception to December 2020. Consensus was obtained using the Research and Development/University of California, Los Angeles Appropriateness Method. Results were summarized using the Grading of Recommendations Assessment, Development, and Evaluation method. We developed five expert consensus statements and two recommendations in answer to two questions: what laboratory tests and physiologic triggers should guide the decision to administer a platelet or plasma transfusion in critically ill children; and what product attributes are optimal to guide specific product selection? Conclusions: The Transfusion and Anemia EXpertise Initiative–Control/Avoidance of Bleeding program provides some guidance and expert consensus for the laboratory and blood product attributes used for decision-making for plasma and platelet transfusions in critically ill pediatric patients. Abstract : Supplemental Digital Content is available in the text.